Identity Imperialism and Nation Building: Governance, Corruption, and Separatism in Nigeria - Oguejiofor, Princewilliams Odera; Akogwu, Chukwunonso Joseph; Okonkwo, Arinze Emmanuel (JPW (Jurnal Politik Walisongo), 2025)
This paper studies how Nigeria’s national unity, governance, and socioeconomic growth have been structurally weakened by the externally imposed identity that was a legacy of British colonialism. It also examines how this has fuelled ethnic polarisation, corruption, and separatist movements. Based on the Centre-Periphery and Psycho-Cultural Conflict theories, the study uses qualitative content analysis of secondary data to explain how imposed colonial identity impedes genuine nation-building and good governance. By methodically connecting identity imperialism to deficiencies in governance and development issues, this study closes a significant gap. The way that legal frameworks sustain identity fragmentation is further demonstrated by an analysis of the 1999 constitutional of Nigeria. The study concluded with evidence-based recommendations that highlight constitutional changes that promote fiscal federalism and inclusive national discourse as necessary conditions for long-term national development and cohesion.